Manajemen Sekolah Sebagai Pilar Penyelenggaraan Kantin Sehat - Kadaryati, Sri; Prasetyaningrum, Yunita Indah; Sukismanto, -; Wulan, Yuni Kartika; Wardani, Desy Fitria; Nareswara, Angelina Swaninda (Jurnal Gizi, 2023)
Eating habits, nutritious and safe food intake are greatly determined the nutritional status  of school-age children and adolescents. Eating habits acquired during adolescence will have an impact on adulthood and the elder. Overweight and obesity increased not only occur in adults, but also in adolescents. A school is a place where children spend more time every day than at home. Therefore, it needs to be considered food provision in schools. This study provides an overview of the readiness of school management in implementing healthy canteens in schools. This was qualitative research with a case study approach. The research was conducted at SMP Negeri 4 Depok Sleman Yogyakarta from June to August 2022. Data were collected using in-depth interviews involving principals and teachers as narasumberts. The study has obtained an Ethical Clearance from Komisi Etik Penelitian Kesehatan, Fakultas Ilmu Kesehatan, Universitas Respati Yogyakarta. The results showed that the school had prepared buildings and physical facilities in the canteen. The policy of providing healthy food was indicated by menu selection with restrictions on products high in sugar and salt, as well as the selection of safe serving utensils. This policy was agreed upon by the seller in the cooperation agreement between the school and the seller. Supervision systems were implemented by appointing healthy canteen management teams. Based on the results of this study, it was concluded that school management was committed to realizing a healthy canteen in schools. Policies regarding the provision of healthy food can be improved by adding menu choices from the vegetable group. Food safety can be improved by setting the serving time of food served.Keywords: healthy canteen, school management, principals, teachers